1991
DOI: 10.1364/ao.30.000597
|View full text |Cite
|
Sign up to set email alerts
|

Elements of a unique bacteriorhodopsin neural network architecture

Abstract: A rapidly reprogrammable neural network architecture with the possibility for a large synapse matrix is presented. The concept is based on the use of bacteriorhodopsin as a molecular computational element with electrooptical characteristics that are associated with a series of intermediates that are photochemically initiated. One of these states has been stabilized by several orders of magnitude with specific environmental conditions, and this allows the concentration of intermediates to be readily affected wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…In addition, the current conformational state can be easily detected by using light because the adsorption spectra of bacteriorhodopsin depends on its conformational state [18]. Potential applications of bacteriorhodopsin are high-density memories [23], hybrid electro-optical neural networks [60], and optical pattern recognition [59]. DNA Computing Because DNA Computing is now a well established special branch of RCC, we will not discuss it in much detail here, but only give a short introduction.…”
Section: Real Chemical Computingmentioning
confidence: 99%
“…In addition, the current conformational state can be easily detected by using light because the adsorption spectra of bacteriorhodopsin depends on its conformational state [18]. Potential applications of bacteriorhodopsin are high-density memories [23], hybrid electro-optical neural networks [60], and optical pattern recognition [59]. DNA Computing Because DNA Computing is now a well established special branch of RCC, we will not discuss it in much detail here, but only give a short introduction.…”
Section: Real Chemical Computingmentioning
confidence: 99%
“…Nevertheless the possibility to interface BR electrically is the basis for several suggested applications. The use of BR in optical sensors for acquiring and low-level processing of the input signal [164,165,166], and the BR-based optically reprogrammable artificial neural network design [167,168] illustrated in Fig. 10, are examples.…”
Section: Bacteriorhodopsin: a Photonic Automatonmentioning
confidence: 99%
“…A limited number of bR studies in non-aqueous environments have been previously reported [9][10][11][12][13][14] as well as studies of current flow through PM patches [15,16].…”
Section: Introductionmentioning
confidence: 99%